THE ROLE OF THE PHYSICAL THERAPIST IN CHILDREN WITH NEUROPSYCHOMOTOR RETARDATION DIAGNOSED WITH RETT SYNDROME - Nayelle Ferreira de Sousa, Sara; da Silva Araújo, Cintia; Cardoso Azevedo, Lígia; Silva de Oliveira, Elen; Sacramento Santana, Uilma; dos Santos Silva, Francielly; Carvalho Andrade, Maycon; Mendes dos Santos, Jéssica (Health and Society, 2022)
Introduction: Rett syndrome was initially described as a condition of “Cerebral atrophy associated with hyperammonemia”, by german pediatrician Andreas Rett in a study with 31 girls, where mental and motor regression was noticeable in these patients. It is a genetic syndrome, associated with mutations in the MECP2 gene, located on the X chromosome. SR, being considered rare, and despite the difficulties caused by the condition of the syndrome, these children can survive until adulthood, although with low life expectancy compared to normal individuals. Objective: To verify in the literature the physical therapy approaches used in children with neuropsychomotor retardation diagnosed with Rett syndrome. Materials and Methods: This study is characterized as an integrative review of the literature. Data collection was performed from May to June 2021, using Lilacs, PubMed and Medline electronic databases. The Boolean descriptors and operators used were Rett syndrome AND Physiotherapy intervention. Articles previously or equal to the year 2021 were included in the sample, in English and Portuguese. Results: The physiotherapist has several options of therapies, from the conventional to the alternatives. Regarding the importance of physiotherapy in patients with Rett Syndrome, it is seen that it has great relevance for the extension of survival of these individuals, being a fundamental part in the management of the syndrome. Conclusion: The research demonstrated that the role of the physiotherapist in children diagnosed with Rett syndrome has been of incredible significance, since these professionals provide these children with the opportunity to perform their daily activities in a more functional and often less painful way, this is because children with Rett syndrome have a delay in neuropsychomotor development, which contributes in the future to an adult with consequences that hinder simple day-to-day activities.